Will Imatinib Compromise Reproductive Capacity? - Zamah, Alberuni M. (AlphaMed Press, 2011)
Imatinib mesylate is the first in a family of highly effective, minimally toxic, targeted agents used widely to treat Philadelphia-positive leukemias and selected other cancers, leading to a steady rise in the prevalence of patients using such therapy. Because failure of therapy would require conventional gonadotoxic chemotherapeutics, many female patients using imatinib may choose to preserve fertility. Herein, we provide evidence of a potential negative effect of imatinib on ovarian function by reporting the first case of a woman who showed a severely compromised ovarian response to gonadotropin stimulation while on imatinib, with a normal ovarian response after stopping this medication.